(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The specific purpose of the study was to see the effect of concentrative meditation on human brain Activity/Wave with well planned, systematically developed program of meditation.The statistical analysis of data collected on sixteen subjects of age group ranging between 20-25 years belonging to different groups. The subjects were divided randomly into two equal groups consisting of eight subjects each; belonging to group I (concentrative meditation) and group II (control group).The data for Neuro-Physiological variable were collected five times in the progressive manner that is before the start of the experiment as pre-test and after the 3rd, 6th, 9th and 12th week along with EEG as to record the progressive performance of the subjects. Finally at the end of 12 weeks the training programme was concluded. The treatment was given six days in a week.To compare the results, analysis was done through frequency analysis and spectral analysis in numeric form with the help of FFT (Fast Fourier Transform) which converted brain Activity/Wave (Hertz) in to numbers by the electronic encephalogram (Sixteen channels) and EEG Analysis Software super Spec version 4.2.6 (RMS). Statistical analysis was done with the help of SPSS 2007 and the trend was used to see the effectiveness of meditation on different brain waves by comparing their magnitudes.Alpha frequency is the prominent frequency of occipital area and the emphasis of the present study was on the alpha frequency band, the analysis was done for the readings from the occipital region (O1 and O2) with time bound of two minute to transform the wave frequency in the digital form. Digital filters were computer algorithm that took a digitized signal and transformed it by filtering some frequencies. The most common band-pass was from 1 Hz to 50 Hz. In the present study, it was sufficient to have frequency band in the range from 1 Hz to 25 Hz and the data were expressed in μV2/Hz.